Growth Hormone Secretagogue Receptor 1A Antagonist JMV2959 Effectively Prevents Morphine Memory Reconsolidation and Relapse - Zhao, Jing; Du, Xinyu; Chen, Mingzhu; Zhu, Shimin (Frontiers in Pharmacology, 2021)
Relapse to drug seeking after prolonged abstinence is a major problem in the clinical treatment of drug addiction. The use of pharmacological interventions to disrupt established drug reward memories is a promising strategy for the treatment of drug addiction. A growth hormone secretagogue receptor 1A antagonist, JMV2959, has been shown to reduce morphine-induced conditioned place preference (CPP) in rats within hours of intervention; thus, JMV2959 is a potential candidate for drug addiction treatment. However, the effect of JMV2959 on reconsolidation to disrupt drug seeking remains unknown. In this study, we assessed the effect of JMV2959 on morphine induced memory reconsolidation to inhibit drug seeking after drug withdrawal. Our results showed that the administration of JMV2959 (6 mg/kg) significantly reduced environmental cue induced CPP, which suggested a disruptive effect of JMV2959 on morphine induced memory reconsolidation. Additionally, JMV2959 administration significantly altered the locomotor activity and food and water intake but did not significantly alter the natural reward preference. We concluded that JMV2959 may be an effective candidate to treat drug addiction.